Regional Labor Market Integration, Shadow Wages and Poverty in Vietnam. (January 2017) - Trung, Le Dang; Oostendorp, Remco H.
Highlights: Regional labor markets are increasingly integrated in terms of market wages. Shadow wages in farm self-employment remain a fraction of market wages in Vietnam. Labor market disintegration explains the low value of labor time of poor workers. Labor market policies should focus more on within-region labor market integration. Summary: Poor workers suffer from low returns to their most abundant resource, labor. In this paper we show that labor market integration strongly affects these returns for poor workers in Vietnam. Using seven representative household surveys, it is shown that while regional labor markets have become increasingly integrated over the period 1993–2010 considering market wages of workers in wage employment, there remains a strong lack of integration considering shadow wages of workers in farm self-employment. Shadow wages have been increasing as a proportion of market wages during 1993–2010, but they remain only 22–28% of rural market wages by 2010. Using a decomposition technique, it is shown that the lack of integration between the farm self-employment segment with various segments of wage employment (regional, urban versus rural, non-farm household versus other enterprises), explains primarily the gap in returns to labor between poor and non-poor workers. These findings show that labor market integration studies should not only focus on observed market wages but also on shadow wages in order to understand the relationship between labor market integration and the returns to labor.